2002
DOI: 10.1073/pnas.232591099
|View full text |Cite
|
Sign up to set email alerts
|

Bornyl diphosphate synthase: Structure and strategy for carbocation manipulation by a terpenoid cyclase

Abstract: The x-ray crystal structure of dimeric (؉)-bornyl diphosphate synthase, a metal-requiring monoterpene cyclase from Salvia officinalis, is reported at 2.0-Å resolution. Each monomer contains two ␣-helical domains: the C-terminal domain catalyzes the cyclization of geranyl diphosphate, orienting and stabilizing multiple reactive carbocation intermediates; the N-terminal domain has no clearly defined function, although its N terminus caps the active site in the C-terminal domain during catalysis. Structures of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
430
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(451 citation statements)
references
References 35 publications
14
430
4
3
Order By: Relevance
“…Similar findings have been reported with other terpene synthases, 17,18 suggesting that the use of the charged PP·Mg complex as a counter ion to stabilize proximal secondary carbocation intermediates may be a relatively common enzymatic mechanism utilized by these enzymes. However, such counter ion stabilization seems to be limited to carbocations located relatively close to the original PP position, as indicated by the weaker synergy exhibited by distal aza analogues and structural studies.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar findings have been reported with other terpene synthases, 17,18 suggesting that the use of the charged PP·Mg complex as a counter ion to stabilize proximal secondary carbocation intermediates may be a relatively common enzymatic mechanism utilized by these enzymes. However, such counter ion stabilization seems to be limited to carbocations located relatively close to the original PP position, as indicated by the weaker synergy exhibited by distal aza analogues and structural studies.…”
Section: Discussionsupporting
confidence: 83%
“…However, such counter ion stabilization seems to be limited to carbocations located relatively close to the original PP position, as indicated by the weaker synergy exhibited by distal aza analogues and structural studies. 17,19 Indeed, it has been suggested that the PP·Mg anion may drive reactions towards localization of the carbocation intermediates close to the negative charge, particularly in the absence of other stabilizing influences in the active site. 11 Finally, the fact that ent-beyeran-16-yl PP does not appear to be a free intermediate further emphasizes the tight control KS must exert over the ionized carbocation intermediates and PP·Mg anion within its active site to prevent recombination of the closely associated ion pair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These first structures were followed shortly thereafter by those of trichodiene synthase 79 and aristolochene synthase (Figure 11b), 80,81 In collaboration with Rod Croteau, David's laboratory also solved the crystal structure of the monoterpene synthase, bornyl diphosphate synthase. 82 These studies confirmed the universal all-helical fold of the sesquiterpene and monoterpene synthases, and have provided detailed pictures of the organization of the active sites of these remarkable, synthetically versatile cyclases. 76,[83][84][85][86] Complementing and enriching these studies, Prof Dean J Tantillo (U. C. Davis) has deepened the understanding of the mechanisms and energetics of terpene cyclization reactions through detailed quantum chemical calculations of the reaction pathways linking carbocationic intermediates and transition state structures for a wide variety of terpene synthase-catalyzed reactions.…”
Section: Enzymology and Molecular Genetics Of Natural Product Biosyntmentioning
confidence: 59%